Różnice deklarowanej częstości samokontroli stanu zdrowia u osób pracujących w zawodach medycznych i pozamedycznych = The difference between the declared frequency of self-health monitoring carried out by representatives of the medical and the non-medical professions - Nowicki, Grzegorz Józef; Rudnicka-Drożak, Ewa; Ślusarska, Barbara; Piasecka, Honorata; Zarzycka, Danuta; Brodowicz-Król, Magdalena (Journal of Education, Health and Sport, 2016)
Nowicki Grzegorz Józef, Rudnicka-Drożak Ewa, Ślusarska Barbara, Piasecka Honorata, Zarzycka Danuta, Brodowicz‑Król Magdalena. Różnice deklarowanej częstości samokontroli stanu zdrowia u osób pracujących w zawodach medycznych i pozamedycznych = The difference between the declared frequency of self-health monitoring carried out by representatives of the medical and the non-medical professions. Journal of Education, Health and Sport. 2016;6(5):236-254. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45122 http://ojs.ukw.edu.pl/index.php/johs/article/view/3522 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 14.05.2016. Różnice deklarowanej częstości samokontroli stanu zdrowia u osób pracujących w zawodach medycznych i pozamedycznych The difference between the declared frequency of self-health monitoring carried out by representatives of the medical and the non-medical professions Grzegorz Józef Nowicki1, Ewa Rudnicka-Drożak2, Barbara Ślusarska1, Honorata Piasecka1, Danuta Zarzycka3, Magdalena Brodowicz-Król3 1. Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Przychodnia Lekarza Rodzinnego, CRH ŻagielMed, ul. Onyksowa 12, 20-582 Lublin 3. Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie dr n. o zdrowiu Grzegorz Józef Nowicki1, dr hab. n. med. Ewa Rudnicka-Drożak2, dr hab. n. o zdrowiu Barbara Ślusarska1, mgr Honorata Piasecka1, dr hab. n. o zdrowiu Danuta Zarzycka3, mgr Magdalena Brodowicz-Król3 1. Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Przychodnia Lekarza Rodzinnego, CRH ŻagielMed, ul. Onyksowa 12, 20-582 Lublin 3. Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Słowa klucze: profilaktyka, zachowania kontroli zdrowia, osoby pracujące Key words: prevention, behavior health checks, people working Streszczenie Wstęp: Uczestnictwo w populacyjnych badaniach profilaktycznych oraz regularne samobadanie narządów to zachowania zdrowotne zmierzające do wczesnego wykrycia chorób. Cel pracy: Określenie różnic w zakresie deklarowanej samokontroli stanu zdrowia (uczestnictwo w programach profilaktyki i samobadania narządów) pomiędzy osobami wykonującymi zawód medyczny i pozamedyczny. Materiał i metody: Badania przeprowadzono wśród 598 dorosłych osób pracujących, wykonujących zawody medyczne i pozamedyczne. Narzędziem badawczym był kwestionariusz ankiety własnego autorstwa. Wyniki: Uzyskane wyniki badań wskazują, że osoby wykonujące zawód niemedyczny istotnie częściej deklarowały uczestnictwo w Ogólnopolskim Programie Profilaktyki Chorób Odtytoniowych (w tym POChP) oraz w Ogólnopolskim Programie Profilaktyki Raka Jelita (p<0,001) niż badani wykonujący zawód medyczny. Natomiast kobiety, które wykonywały zawód medyczny, istotnie częściej deklarowały uczestnictwo w Ogólnopolskim Programie Profilaktyki Raka Szyjki Macicy oraz częściej wykonywały samobadanie piersi. (p<0,001). Wnioski: Istnieje wyraźne zróżnicowanie zachowań kontrolnych stanu zdrowia w badanych grupach. Praca w zawodach pozamedycznych warunkuje pozytywnie częstość uczestnictwa w ogólnopolskich programach profilaktyki chorób cywilizacyjnych. Natomiast regularne samobadanie piersi częściej deklarują kobiety wykonujące zawód medyczny. Abstract Introduction: Participation in national disease-prevention programmes and regular self-examinations are health-related activities that facilitate early diagnoses. Objective: The determination of the difference between the declared extent of self-health monitoring (participation in disease prevention programmes and self-examinations) carried out by representatives of the medical and the non-medical professions. Materials and methods: The research was conducted with 598 adults employed in the medical and the non-medical professions. The research tool was a questionnaire prepared by the researcher. Results: The results obtained indicate that persons employed in the non-medical professions significantly more often declared participation in the Nationwide Smoking-Related Disease Prevention Programme (including the COPD), and the Nationwide Bowel Cancer Prevention Programme (p<0.001), than subjects who worked in the medical professions. Women employed in the medical professions, on the other hand, significantly more often than women in the non-medical professions declared participation in the Nationwide Cervical Cancer Prevention Programme and more frequently performed breast self-examinations (p<0.001). Conclusion: There is a significant difference in health-monitoring practices found between the examined groups. Employment in non-medical professions positively influences participation in nationwide civilisation-diseases prevention programmes, whereas regular breast self-examination is more often declared by women who work in the medical professions than by women in the non-medical professions.